Challenges of Online English Language Teaching and Learning at Secondary Schools in Bangladesh - Nishat Tasneem (Universitas Islam Negeri (UIN) Mataram, 2022)
Virtual classrooms manifest a burgeoning pedagogic instrument in current English language teaching and learning contexts around the globe; the use of which was significantly increased with the onset of the COVID-19 pandemic crisis. Such practices can also be traced to the secondary-level educational context in Bangladesh. Alike the traditional classroom, these virtual classrooms are not without challenges. To unravel such challenges of online English classes at the secondary level in a developing country context like Bangladesh, a qualitative research framework was used in this research. As such, the current study utilized qualitative data collection instruments to collect in-depth information about the individual, course, contextual and technological challenges of online English language education at the secondary level in Bangladesh, based on Anderson and Grönlund’s (2009) conceptual framework of online education in developing countries. The data was collected from both the learners and the facilitators of such online English language classes and analyzed based on the codes from the conceptual framework of the study. Moreover, data regarding the pedagogic participant-oriented suggestions to encounter such challenges were also collected and analyzed. The findings of the study highlight a range of different pedagogic and contextual challenges in relation to online English education in a developing country context like Bangladesh and draw on its implication to address policy issues as well as pedagogic practices